Mini shopaholic - Kinsella, Sophie (Black Swan, 2010)
Shopaholic Becky Brandon (nee Bloomwood)'s two-year-old is ... spirited. She knows what she wants, whether it's a grown-up Prada handbag or a toy pony (40% off, so a bargain, surely?) When yet another shopping trip turns to mayhem, Becky decides it's time to give Minnie her own pocket money. Is it a bad sign when Minnie goes instantly overdrawn? Minnie isn't the only one in financial crisis. As the Bank of London collapses, people are having to Cut Back. Everyone needs cheering up, so what better way to do it than to throw a fabulous surprise party? A thrifty party, of course. Except economising and keeping a secret have never been Becky's strong points...